The impact of immune cell interactions on virus quasi-species formation - Ali Moussaoui; Vitaly Volpert (Mathematical Biosciences and Engineering)
The process of viral infection spreading in tissues was influenced by various factors, including virus replication within host cells, transportation, and the immune response. Reaction-diffusion systems provided a suitable framework for examining this process. In this work, we studied a nonlocal reaction-diffusion system of equations that modeled the distribution of viruses based on their genotypes and their interaction with the immune response. It was shown that the infection may persist at a certain level alongside a chronic immune response, exhibiting spatially uniform or oscillatory behavior. Finally, the immune cells may become entirely depleted, leading to a high viral load persisting in the tissue. Numerical simulations were employed to elucidate the nonlinear dynamics and pattern formation inherent in the nonlocal model.